Islamic Public Finance Instruments According to Kitab Al Amwal by Ad Dawudi - Siti Mudrikah; Muhamad Nafik H Ryandono (AFEBI Islamic Finance and Economic Review, 2021)
Islamic public finance is a theme that has been discussed by several previous scholars, such as Ad Dawudi in his book AL Amwal. In this paper, the author examines his writings on the source of state finance through state revenue, namely zakat. Zakat according to Ad Dawudi has a role to eliminate social disparities between the rich and the poor, creating a high sense of solidarity. This study uses a literary study of the book Al Amwal by Abu Ad Dawudi as the first source. His thinking said that zakat was able to provide economic support, even his thoughts were used in the Fatimid government. At that time, his country was experiencing the chaos of corruption and social inequality. Then the incident is relevant to the state of declining economic growth in Indonesia, one of which is marked by increasing poverty. Ad Dawudi's thought regarding zakat is expected to be able and relevant to be used to make policies in Indonesia, especially Indonesia has the largest Muslim community.Keyword: Ad Dawudi, Islamic Public Finance, Zakat, Poverty, Islamic Economics